Distribusi Hama Serangga pada Tanaman Lada di Kabupaten Bangka Selatan: Distribusi Hama Serangga pada Tanaman Lada di Kabupaten Bangka Selatan - Ropalia; Rion Apriyadi; Herry Marta Saputra (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
Productivity of white pepper has steadily decreased in the last five years. One of the limiting factors the production of white pepper plantations in Bangka is the pest attack. This research was conducted to determine distribution of insect pests in the white pepper plantations in South Bangka Regency, which is the centre of white pepper production in the Bangka Belitung Islands Province. This research was conducted by observing and detemining the white pepper plantations using purposive sampling methode. The results found two insect families that dominate in the white pepper plantations, namely the coreidae which is a family of Dasynus piperis, fruit-sucking pests and the fimicidae, not a pest. The insect diversity index in the low to medium category, the richness index in the low category, and evenness index in the medium category.